POLIGAMI PERSPEKTIF PEREMPUAN MUSLIM INDEPENDEN: RELEVANSI SOSIAL KRITIS KEMASLAHATAN KELUARGA DAN KESTABILAN BATIN KONTEMPORER - Jasmin, Suriah Pebriyani; Sylviah; Satriani (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2026)
This study aims to explore the perspectives of independent Muslim women in Bone Regency who demonstrate openness toward polygamy and perceive it as a component of Islamic teachings with the potential to promote family welfare. The focus of the research is directed at examining the lived experiences and intellectual constructions of women engaged in polygamous households, as well as independent women who are not involved in polygamous relationships but nonetheless hold positive views toward the practice.This study seeks to understand how religious rationality, social experience, and emotional maturity shape their perceptions, such that polygamy is not interpreted as a form of female subordination, but rather as an alternative model of marital relations capable of fostering emotional stability, mental well-being, and family harmony when practiced in accordance with principles of justice.This research constitutes a field study conducted in Bone Regency. It employs several approaches, including an empirical sociological approach, a phenomenological approach, a maqāṣid al-syarī‘ah approach, and an Islamic gender approach. Data were collected through in-depth interviews and observations involving purposively selected informants. The informants consisted of independent women with diverse experiences related to polygamy. Data analysis was carried out through stages of data reduction, data display, and inductive conclusion drawing.The findings indicate that independent women who are open to polygamy perceive it as a space for the actualization of spiritual and emotional maturity. Polygamy is understood as having the potential to alleviate emotional burdens, create a sense of security, and sustain financial support and attention when managed justly. This study contributes academically to contemporary Islamic family studies by presenting the positive perspectives of independent women, who are rarely positioned as primary subjects in polygamy discourse. These findings may serve as a reference for the development of family education programs, the strengthening of marital counseling, and the enrichment of gender discourse grounded in women’s empirical perspectives